2013
DOI: 10.1111/sms.12150
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of atrial fibrillation among elderly Norwegian men with a history of long‐term endurance sport practice

Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia. The prevalence increases with increasing age. In middle-aged men, endurance sport practice is associated with increased risk of AF but there are few studies among elderly people. The aim of this study was to investigate the role of long-term endurance sport practice as a risk factor for AF in elderly men. A cross-sectional study compared 509 men aged 65–90 years who participated in a long-distance cross-country ski race with 1768 men aged 65–87 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
81
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 34 publications
8
81
0
1
Order By: Relevance
“…A total of 22 studies comprising of 656,750 participants were analyzed in this meta‐analysis, which included 12 cohort studies (including 4 prospective cohorts), 5 case‐control, 1 post hoc analysis of randomized controlled study, 1 prospective observational, 1 retrospective, and 2 cross sectional studies. The age of study participants ranged from 50 to 61 years (interquartile range). The study designs and participant characteristics are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 22 studies comprising of 656,750 participants were analyzed in this meta‐analysis, which included 12 cohort studies (including 4 prospective cohorts), 5 case‐control, 1 post hoc analysis of randomized controlled study, 1 prospective observational, 1 retrospective, and 2 cross sectional studies. The age of study participants ranged from 50 to 61 years (interquartile range). The study designs and participant characteristics are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…3,7,8 Our results showed that moderate amounts of exercise are beneficial for patients with AF; these results support the growing evidence of an exercise-induced protective effect on AF risk in healthy individuals. Light to moderate amounts of exercise seem to reduce AF risk, 13,15,16 and better cardiorespiratory fitness is shown to have a graded, inverse relationship to AF risk up to a certain point. 28,29 Our study results extend these previous findings by also showing a reduced burden of AF in individuals with manifest disease.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Other studies indicate a lower incidence of AF in individuals performing more moderate levels of exercise. 13,15,16 Because of these conflicting findings, many AF patients and their physicians have been uncertain about the benefits and potential negative effects of exercise training and have therefore been reluctant to partake in endurance exercise, particularly at higher intensities. The purpose of the present study was to evaluate the effect of 12 weeks of aerobic interval training (AIT) on time in AF, AF symptoms, cardiac function, exercise capacity, quality of life (QoL), lipid profile, and the need for healthcare services in patients with paroxysmal or persistent AF.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, endurance sport participation seems to be an independent risk factor for AF in men aged 65 years. 6 The aim of this study was to assess the dose-response relation between cumulative years of endurance exercise and risk for atrial arrhythmias in men aged 53 years. …”
mentioning
confidence: 99%